2011
DOI: 10.1007/s11743-011-1252-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Cationic Gemini Surfactant and the Corresponding Monomeric Surfactant for Corrosion Protection of Mild Steel in Hydrochloric Acid

Abstract: A cationic gemini surfactant, N,N 0 -didodecyl-N,N,N 0 ,N 0 -tetramethyl-1,4-butanediammonium dibromide (12-4-12) and the corresponding monomeric surfactant dodecyltrimethylammonium bromide were compared with respect to corrosion inhibition efficiency in 1 M hydrochloric acid solution. Polarization and electrochemical impedance spectroscopy were used to evaluate corrosion inhibition. The 12-4-12 surfactant showed an extremely high corrosion inhibition efficiency at very low concentration. Surface tension meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The corrosion inhibition efficiencies (η %) of the inhibitors were obtained from Eqn and are listed in Table : η%=[]()Rctitalic,iitalic‐Rctitalic,bRctitalic,i×100where R ct,b and R ct,i are the charge transfer resistances of the samples when immersed in hydrochloric acid solution without and with inhibitors, respectively. The highest corrosion inhibition efficiency 97% obtained in 10 mM indole‐3‐acetic acid contained solution.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion inhibition efficiencies (η %) of the inhibitors were obtained from Eqn and are listed in Table : η%=[]()Rctitalic,iitalic‐Rctitalic,bRctitalic,i×100where R ct,b and R ct,i are the charge transfer resistances of the samples when immersed in hydrochloric acid solution without and with inhibitors, respectively. The highest corrosion inhibition efficiency 97% obtained in 10 mM indole‐3‐acetic acid contained solution.…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of compound A (3.00 g, 10.44 mmol) and 1-bromotetradecane (8.72 g, 31.49 mmol) in acetone (30 mL) was refluxed for 24 h. After the reaction mixture had cooled to room temperature, the crude product was isolated by filtering and then recrystallized twice from a mixture of acetone and acetonitrile to give 14-DEHA-14 as white crystal (8.04 g, yield 91.60 %). 1 H NMR (400 MHz, CDCl 3 ) d ppm: 0.86-0.89 (t, J = 6.8 Hz, 6H, 2(CH 2 ) 11 CH 3 ), 1.25-1.36 (m, 44H, 2(CH 2 ) 11 CH 3 ), 1.70-1.77 (m, 8H, CH 2 CH 2 CH 2 CH 2 and 2CH 2 CH 2 (CH 2 ) 11 ), 2.44 (m, 4H, 2CH 2 COO), 3.48 (s, 12H, 4NCH 3 ), 3.62-3.66 (t, J = 7.6 Hz, 4H, 2 NCH 2 CH 2 (-CH 2 ) 11 )…”
Section: Synthesis Of 14-deha-14mentioning
confidence: 99%
“…Use of corrosion inhibitors is one of the most convenient means for protecting metals against corrosion, especially in acidic media [1,2]. Most organic corrosion inhibitors interact with the metal surface through heteroatoms, such as nitrogen, oxygen, phosphorus, sulfur, aromatic rings, and multiple bonds, which can markedly change the corrosion resistance of the metal [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Gemini surfactants [6,7] (a new generation developed in recent years) consist of two hydrophilic groups and two hydrophobic groups that are separated by a rigid or flexible spacer in a molecular structure. It has been demonstrated that the properties of these new surfactants are superior to those of conventional surfactants, and include better solubility in water, better effect in lowering the surface tension of water, more efficient in forming micelles, etc.…”
Section: Introductionmentioning
confidence: 99%